Biology and Control of Japanese Climbing Fern (Lygodium japonicum): FOR 218/FR280, 5/2009 - Minogue, Patrick J.; Jones, Stella; Bohn, Kimberly K.; Williams, Rick L. (EDIS, 2009)
FOR-218, a 7-page illustrated fact sheet by Patrick J. Minogue, Stella Jones, Kimberly K. Bohn, and Rick L. Williams, describes this non-native, invasive vine which is widespread in damp areas in north and West Florida — its biology and control measures. Includes references. Published by the UF School of Forest Resources and Conservation, May 2009. FOR 218/FR280: Biology and Control of Japanese Climbing Fern (Lygodium japonicum) (ufl.edu)